2010
DOI: 10.1089/acm.2009.0281
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Propolis Extract Against Yeasts Isolated from Vaginal Exudates

Abstract: The PE showed an outstanding performance against the tested vaginal yeast strains, and could be included among the novel therapeutic options for the treatment of vulvovaginal candidiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
12
33
0
1
Order By: Relevance
“…3,14 Similarly to our results, Brumar et al 7 also reported a high cure rate with fluconazole (85.71%) in diabetic women with VVC. We acknowledge that the number of diabetic women in our study was small, and that this group may not fully represent populations of diabetic women.…”
Section: 13supporting
confidence: 87%
“…3,14 Similarly to our results, Brumar et al 7 also reported a high cure rate with fluconazole (85.71%) in diabetic women with VVC. We acknowledge that the number of diabetic women in our study was small, and that this group may not fully represent populations of diabetic women.…”
Section: 13supporting
confidence: 87%
“…As far as the constituents that are probably responsible for the antifungal effects are concerned, they are comparable with propolis samples originating from other countries reported in the literature [20][21][22][23][24][25][26][27][28][29][30][31][32]. Future research of propolis is needed, particularly in the field of isolation and detailed description of its biologically active compounds.…”
Section: Discussionsupporting
confidence: 62%
“…The inhibitory effect of propolis on pathogenic fungi, including yeasts and dermatophytes, have been described by many investigators [6,20,22,26,27]. Most of these experiments tested propolis as ethanolic extract (EEP), so it was difficult to specify a component responsible for a specific antifungal effect except for flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] As propolis has characteristics that are beneficial to human health, such as antioxidant, anti-inflammatory, antifungal and anticancer activities, its chemical composition and properties have been extensively studied. [7][8][9][10] The antioxidant activity of ethanolic extracts of propolis has been evaluated by free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH • ) scavenging, 8 by the ferric reducing ability power (FRAP) using the ferric-tripyridyltriazine (Fe 3+ -TPTZ) complex 11 and by oxidation of linoleic acid. 5 Similarly, mass spectrometry analyses has been used to examine the chemical composition of propolis extracts and its correlation with type and properties.…”
Section: Introductionmentioning
confidence: 99%